Effects of fire fight safety education when applied metaverse in Korea: Focusing on the construction industry - Moon, Pil-Jae; Kong, Ha-Sung (Journal of Education and e-Learning Research, 2023)
This study reviewed educational, aesthetic, entertainment and deviant experiences which are elements of the metaverse experience set them as research variables and presented the results of the study through a survey. First, it was found that the educational experience was statistically significant for safety education satisfaction and had a positive effect. In order to provide practical education, educational experiences must feel like reality and fun content must be easily delivered. Second, it was found that deviant experiences were statistically significant for safety education satisfaction and had a positive effect. This can be said to increase the prevention of safety accidents only when the deviant experience service feels like reality and interesting contents related to safety education are easily delivered. Third, it was found that the aesthetic experience was statistically significant for safety education satisfaction and had a positive effect. This can be said to increase the prevention of safety accidents only when aesthetic experiences and services feel like reality and interesting contents related to safety education are easily delivered. Fourth, it was found that the recreational experience was statistically significant for safety education satisfaction and had a positive effect. This can be said to increase the prevention of safety accidents only when entertainment and deviant experience services feel like reality and interesting contents related to safety education are easily delivered.